THE INFLUENCE OF ADVERTISING DISCLOSURE AND CELEBRITY-PRODUCT CONGRUENCE ON CONSUMER PURCHASE INTENTION IN SOCIAL MEDIA : Pengaruh Advertising Disclosure dan Celebrity-Product Congruence Terhadap Minat Pembelian Konsumen Di Social Media - Silvina Maulidya; Perengki Susanto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Idonesia is among the 10 countries with the highest percentage of internet users who frequently shop online. Indonesian consumer behavior has also shifted. People now tend to seek information and product recommendations through digital platforms before making a purchase. This study aims to review the influence of Advertising Disclosure and Celebrity-Product Congruence on sponsored advertisements on social media on Consumer Purchase Intention on Social Media. The population in this study were consumers who were active on social media in Padang City. While the number of samples in this study was 257 respondents. Data collection was carried out by distributing questionnaires directly online via Google Form and data processing was carried out using Smart PLS 4.0 software.The findings of this study indicate that: Advertising Disclosure has a positive and significant influence on Consumer Purchase Intention, Celebrity-Product Congruence has a positive and significant influence on Consumer Purchase Intention, In the current study provides insight into the relationship between Advertising Disclosure, Celebrity-Product Congruence, and Consumer Purchase intention on beauty influencer content on Social Media Tiktok. Therefore, with new findings, this study expands the literature the relationship between Advertising Disclosure and Celebrity-Product Congruence on consumer purchase intention in the West Sumatra region